SIFAT PAPAN WOL KAYU DARI POHON TUSAM DISADAP DAN TIDAK DISADAP - I Sulastiningsih M Sulastiningsih; Rozak Memed; Paribroto Sutigno (Jurnal Penelitian Hasil Hutan, 1988)
The  results  of  a  study on  the properties   of  wood-wool  board  made  from  tapped  and  untapped  pine   (Pinus  merkusii Jungh  et de Vriese)  is reported  in this paper.  The  wood  is obtained  from West Java.The result shows  that  hydration   temperature   of tapped  tree  is 36oC,  and untapped   pine  is  43°C. Based on this data, wood  from   tapped  pine  tree can be classified as medium  and that from  untapped  pine  as good  for wood-wool   board material. In general  the  wood-wool  board properties of  both  wood  sources  meet DIN standard.  The effect  of  tapping,  cement proportion, kind  of catalyst,  and interaction  between  cement  proportion  and kind  of catalyst  on the mechanical  properties of wood-wool board are significant.  Tapped pine  is better  than untapped  pine  as raw material for wood-wool board.